PENGARUH KUALITAS FILM DAN KUALITAS LAYANAN TERHADAP MINAT MENONTON (STUDI PADA PENONTON BIOSKOP CINEMA XXI DI TRANSMART PADANG) - Mardianto, Dedi; Syahrial; Deby Handayani (MANABIS: Jurnal Manajemen dan Bisnis, 2022)
The study aims to test simultaneously and partially the influence of film quality, community effects and service quality on interest in watching the Cinema XXI on the Transmart Padang. The use of this variable is expected to find out the factors that influence interest in watching the product (film). This study uses a sample of 100 respondents, namely moviegoers in the Transmart Padang through distributing questionnaires using the non random sampling method. The results of the study showed that film quality, community effects and service quality had a positive effect on interest in watching.